Personality Profiles that Put Users at Risk of Perceiving Technostress - Katharina Pflügner; Christian Maier; Jens Mattke; Tim Weitzel (Business & Information Systems Engineering, 2020)
Some information systems research has considered that individual personality traits influence whether users feel stressed by information and communication technologies. Personality research suggests, however, that personality traits do not act individually, but interact interdependently to constitute a personality profile that guides individual perceptions and behavior. The study relies on the differential exposure-reactivity model to investigate which personality profiles of the Big Five personality traits predispose users to perceive techno-stressors. Using a questionnaire, data was collected from 221 users working in different organizations. That data was analyzed using fuzzy set Qualitative Comparative Analysis. Based on the results, six different personality profiles that predispose to perceive high techno-stressors are identified. By investigating personality traits in terms of profiles, it is shown that a high and a low level of a personality trait can influence the perception of techno-stressors. The results will allow users and practitioners to identify individuals who are at risk of perceiving techno-stressors based on their personality profile. The post-survey analysis offers starting points for the prevention of perceived techno-stressors and the related negative consequences for specific personality profiles.
Keywords: 000; Technostress; Big Five personality traits; Individual differences; Prevention; Dark side of information systems; Differential exposure-reactivity model; Fuzzy set qualitative comparative analysis (fsQCA); Configurations